2022
DOI: 10.15376/biores.17.3.5021-5037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different incising pretreatments in improving permeability in two refractory wood species

Abstract: For many product and applications, the penetration of preservatives or modification substances into wood species should be deep and homogeneous. Caucasian spruce and European larch are resistant to impregnation. This study compared how different incising pre-processes increased the retention of impregnation materials and the depth of their penetration into the structures of these refractory wood species. Mechanical, biological, and laser incising pretreatments were applied to increase the permeability of sapwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…The average wood density in European larch trees (515 to 560 kg/m 3 ) (Karlman et al 2005) is higher than that in Oriental spruce trees (401 to 425 kg/ m 3 ) (Bozkurt et al 1993). In addition, the previous study has demonstrated that the average density (D0: 0.62 g/cm 3 ; D12: 0.64 g/cm 3 ) of larch sapwood is higher than the average density (D0: 0.40 g/cm 3 ; D12: 0.42 g/cm 3 ) of spruce sapwood (Bakir 2022b). Nath et al (2020a) reported that the presence and proportion of earlywood and latewood layers in one annual ring had a significant effect on the incision properties during CO2 laser incision.…”
Section: Effects Of Laser Incision Pretreatment On Microscopic and Wo...mentioning
confidence: 88%
“…The average wood density in European larch trees (515 to 560 kg/m 3 ) (Karlman et al 2005) is higher than that in Oriental spruce trees (401 to 425 kg/ m 3 ) (Bozkurt et al 1993). In addition, the previous study has demonstrated that the average density (D0: 0.62 g/cm 3 ; D12: 0.64 g/cm 3 ) of larch sapwood is higher than the average density (D0: 0.40 g/cm 3 ; D12: 0.42 g/cm 3 ) of spruce sapwood (Bakir 2022b). Nath et al (2020a) reported that the presence and proportion of earlywood and latewood layers in one annual ring had a significant effect on the incision properties during CO2 laser incision.…”
Section: Effects Of Laser Incision Pretreatment On Microscopic and Wo...mentioning
confidence: 88%
“…Nevertheless, maritime pine heartwood is extremely difficult to treat, as evidence of its reduced permeability. Hence, an elevated permeability is worthwhile when wood and wood-based materials must be deeply and homogeneously permeated with chemical or biological products (Bakir 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Delme ön işlemleri emprenye uygulama süreçleri esnasında düşük geçirgenliğe sahip odunlarda hücre içi sıvı akışını iyileştirir (Nath ve ark. 2020ave 2020b, Bakir 2022. Emprenyesi güç ağaç türlerine ait odunların minimum retensiyon ve penetrasyonunu sağlamak için emprenye uygulamalarından önce çeşitli delme ön işlemlerine tabi tutulmaları tavsiye edilir (Islam ve ark.…”
Section: Introductionunclassified
“…Emprenyesi güç ağaç türlerinin mekanik olarak delinmesi ve emprenye edilebilirliği üzerine yapılan çalışmalar genellikle emprenye işlemine tabi tutulmuş odunun penetrasyon ve retensiyon seviyelerine (Perrin 1978, Morris 1995, Winandy ve ark. 1995, Kartal 2002, Bakir 2022 ve mekanik özellikler üzerine etkilerine odaklanmıştır (Winandy ve Morrell 1998, Winandy ve ark. 2022.…”
Section: Introductionunclassified